Innovation in EU merger control: Walking the talk - Reinhilde Veugelers (Bruegel, 2012)
European Union policymakers have in principle put innovation at the heart of competitiveness, in particular in the Europe 2020 strategy. But in merger control, assessments of the innovation effects of mergers are inadequate, even though mergers and acquisitions can have a significant impact on the development of the structure of an industry, and on its capability to innovate. EU merger control rules include scope for assessing the innovation effects of mergers, but in practice, the European Commission's directorate-general for competition (DG COMP) is not 'walking the talk'. Innovation effects are only assessed when claimed by parties to a merger, and this happens rarely. Where innovation effects have been claimed, they have not been decisive in any case, meaning DG COMP has not considered them important enough to influence its decision. A framework should be put in place that makes the reporting of efficiency-related information by the merging parties mandatory, so that innovation effects can be properly assessed for all mergers. In addition, models can be used to make an assessment of the longer-term innovation effects of a merger, and to help inform decision-making.
Keywords: 330; Fusionskontrolle; Innovationsmanagement; EU-Staaten